MANAJEMEN KEBERSIHAN MULUT ANAK SEKOLAH - Purba, Netty Herawaty; Pakpahan, Yohana Fransiska; Nurlela, Siti (LPPM Universitas Awal Bros, 2023)
Cases of cavities and untidy tooth arrangements in elementary school-age children in Batam are still quite high. Poor oral health in children can last into adulthood and get worse if you don't get immediate treatment from a dentist. Unfortunately, this condition is exacerbated by the lack of education and awareness among parents and teachers about children's dental and oral health. The community service activity that will be carried out is in the form of providing education to schoolchildren regarding oral problems in children. The target audience for this s elementary school students. The implementation of community service is carried out by first providing counseling and then providing assistance in the practice of the counseling. As an initial stage, the program will be implemented at public elementary school 10 in Batam City. Conducts counseling about oral and dental health and the growth and development of children's teeth for teachers and guardians of students. Teachers and guardians of students are also provided with information about various bad habits that have the risk of changing the arrangement of a child's teeth, such as biting a pencil, thumb sucking, sucking on the lower lip, incorrect swallowing methods, and an understanding of the impact of excessive consumption of sweet foods or drinks on children's health. dental health. Dental examinations carried out on students provide an overview and good feedback for students, teachers, and parents of students to pay more attention to the health of the child's oral cavity before it's too late, so that the child gets treatment as early as possible.